2012
DOI: 10.1557/opl.2012.709
|View full text |Cite
|
Sign up to set email alerts
|

A Nonzero Gap Two-dimensional Carbon Allotrope from Porous Graphene

Abstract: Graphene is considered one of the most promising materials for future electronic. However, in its pristine form graphene is a gapless material, which imposes limitations to its use in some electronic applications. In order to solve this problem many approaches have been tried, such as, physical and chemical functionalizations. These processes compromise some of the desirable graphene properties. In this work, based on ab initio quantum molecular dynamics, we showed that a two-dimensional carbon allotrope, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
(43 reference statements)
7
21
0
Order By: Relevance
“…Other authors discussed the metallic behavior found for structures obtained by the combination of biphenylenes in several configurations [27] which, despite some structural similarities, are different from the structures discussed in the present work, which can present semiconducting or insulating behavior. One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors discussed the metallic behavior found for structures obtained by the combination of biphenylenes in several configurations [27] which, despite some structural similarities, are different from the structures discussed in the present work, which can present semiconducting or insulating behavior. One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32]. Further, Schlütter et al reported recently that they were able to synthesize octafunctionalized biphenylene GNRs [33].…”
Section: Introductionmentioning
confidence: 99%
“…Octagon and square structures can exist in carbon monolayers [11][12][13][14] .In this work, we try to explore a new 2D allotrope of VA elements with octagons and squares in their structures, as shown in Fig.1. There are five valence electrons in one atom of VA elements, and each atom is bonded to three neighbors similar to the honeycomb structure, so we expect them to have similar structure parameters and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization and calculation of the electronic structure of graphenylene have been reported in Refs. [4,5,6,2]. In these studies, the obtained bandgap values E g sufficiently differ from each other.…”
Section: Introductionmentioning
confidence: 73%